2019
DOI: 10.1016/j.ijpara.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni does not and cannot oxidise fatty acids, but these are used for biosynthetic purposes instead

Abstract: Adult schistosomes, parasitic flatworms that cause the tropical disease schistosomiasis, have always been considered to be homolactic fermenters and in their energy metabolism strictly dependent on carbohydrates. However, more recent studies suggested that fatty acid β-oxidation is essential for egg production by adult female Schistosoma mansoni. To address this conundrum, we performed a comprehensive study on the lipid metabolism of S. mansoni. Incubations with [ 14 C]-labelled fatty acids demonstrated that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Although adult schistosomes cannot oxidize exogenous FA [26], they can use and modify host lipid for biosynthetic purposes by scavenging cholesterol and incorporating FA as phospholipids and neutral lipids in the worm eggs, notably for membrane formation of the developing miracidium [27]. It is therefore tempting to speculate that part of the reduction in some lipoprotein and TG species observed in S. haematobium-infected individuals might result from their active transfer to the eggs produced by female worms and their subsequent elimination in the urine.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Although adult schistosomes cannot oxidize exogenous FA [26], they can use and modify host lipid for biosynthetic purposes by scavenging cholesterol and incorporating FA as phospholipids and neutral lipids in the worm eggs, notably for membrane formation of the developing miracidium [27]. It is therefore tempting to speculate that part of the reduction in some lipoprotein and TG species observed in S. haematobium-infected individuals might result from their active transfer to the eggs produced by female worms and their subsequent elimination in the urine.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…[28][29][30] However, effects of metabolic disorders on Schistosoma and regulation of immune response in many diseases. [31][32][33][34] Therefore, study on the role of ApoE indicates an exciting potential for exploring the mechanism of hepatic immunopathology in schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that host fat are essential elements for development of S mansoni adults and egg production. 33 Since schistosomes cannot produce their own fatty acids, the acquisition of fat from hosts is a key process necessary for egg production. Fecund females have extensive fat stores, mostly in the form of TG, for egg production and cease to produce eggs once their fat reserves exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…PHX is thought to be an inhibitor of carnitine palmitoyl transferase enzymes, namely CPT-1 and CPT-2 and impact long-chain fatty acid metabolism [9,10]. In contrast to previous findings, recent advances in Schistosoma metabolism showed that this parasite lacks CPT-1 and CPT-2 [11][12][13] and that fatty acid oxidation still remains controversial in schistosomes [11,14], therefore the mechanism of action of PHX in this parasite is yet to be clarified.…”
Section: Introductionmentioning
confidence: 90%
“…In mammals, PHX is thought to impact the lipid metabolism by acting as inhibitors of CPT-1 and CPT-2 enzymes [8], whose role is to carry lipids inside mitochondrial for fatty acid oxidation [13]. While the genes encoding CPT-1 and -2 seem to be absent within the Schistosoma genome [11][12][13], in our previous study we demonstrated that female parasites treated with sub-lethal doses of PHX, showed accumulation of lipids within the vitellarium (lipid droplets) [3]. Importantly, the PHX treatment also decreases egg-laying in vitro in agreement with what previously reported on studies with the CPT-1 inhibitor etomoxir, that inhibited depletion of lipid reserves in fecund females worms in vitro and impaired schistosome egg production as well [14].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%